2020
DOI: 10.3390/f11030303
|View full text |Cite
|
Sign up to set email alerts
|

Individual Tree Classification Using Airborne LiDAR and Hyperspectral Data in a Natural Mixed Forest of Northeast China

Abstract: This paper proposes a method to classify individual tree species groups based on individual tree segmentation and crown-level spectrum extraction (“crown-based ITC” for abbr.) in a natural mixed forest of Northeast China, and compares with the pixel-based classification and segment summarization results (“pixel-based ITC” for abbr.). Tree species is a basic factor in forest management, and it is traditionally identified by field survey. This paper aims to explore the potential of individual tree classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…However, it was found that the combination of hyperspectral and LiDAR features could achieve an improvement in accuracy over HSI, and this finding is consistent with the conclusions of independent studies (Dalponte et al, 2012;Hartling et al, 2021). Zhao et al (2020) has pointed out that the average spectrum of the tree canopy can Average spectral curves for different tree species.…”
Section: Discussionsupporting
confidence: 86%
“…However, it was found that the combination of hyperspectral and LiDAR features could achieve an improvement in accuracy over HSI, and this finding is consistent with the conclusions of independent studies (Dalponte et al, 2012;Hartling et al, 2021). Zhao et al (2020) has pointed out that the average spectrum of the tree canopy can Average spectral curves for different tree species.…”
Section: Discussionsupporting
confidence: 86%
“…When implementing the forest restoration method, including group of site preparation operations [53], group of FRM preparation operations , group of seeding [47,54,55] or planting [56,57] on site, it additionally includes group of monitoring operations [58,59]. Alternative rapid analysis [16,31] and encapsulation [60] operations carried out in field conditions using mobile equipment [26,[49][50][51] are additionally introduced into a group of FRM preparation operations.…”
Section: Third Applicationmentioning
confidence: 99%
“…Airborne light detection and ranging (LiDAR) technology obtains horizontal and vertical structural information of ground objects by actively transmitting lasers to targets and receiving point cloud, echo information data [26,27]. In most studies, LiDAR data were often combined with hyperspectral data to improve the classification accuracy [28][29][30][31]. However, the cost of airborne LiDAR data was high, and the processing of airborne LiDAR data was complex, which was not suitable for large-scale forest classification [32].…”
Section: Introductionmentioning
confidence: 99%